Numerical study on interaction of surface cracking and interfacial delamination in thermal barrier coatings under tension - Zhu, W.; Yang, L.; Guo, J.; Zhou, Y.; Lu, Chunsheng (Elsevier BV North-Holland, 2014)
The interaction of surface cracking and interfacial delamination in thermal barrier coatings under tension is investigated by using a cohesive zone finite element model. It is found that the surface crack density has a significant effect on the initiation and propagation of interfacial delamination. The interfacial delamination length decreases with increase of the surface crack density. The influence of ceramic coating thickness and interfacial adhesion parameters on surface cracking and interfacial delamination is discussed. It is shown that the saturated crack densities decrease with increase of the ceramic coating thickness and interfacial delamination length, and the critical surface crack density without interfacial delamination decreases as the interfacial adhesion energy increases. The results imply that the larger the surface crack density and interfacial adhesion energy are, the less the probability of interfacial delamination.